Development Recommendations of Tourist Attractions at Berawa Beach, Tibubeneng, Badung Regency, Bali - Ridwan, Syilpa Regita Putri; Wicaksono, Agus Dwi; Wijayanti, Wawargita Permata; Simamba, Habeenzu (Perencanaan Wilayah dan Kota FT UB, 2024)
Berawa Beach in Bali holds significant potential as a tourist destination due to its natural beauty and vibrant cultural attractions to contribute to the economic growth. However, Berawa Beach faced several problem such as inadequate amenities, accessibility issues, and infrastructure deficiencies hinder its ability to meet tourist expectations and contribute fully to the local economy. This study evaluates the quality of existing tourist attractions identified by 5A concepts framework (Attractions, activities, accessibility, accommodations, and amenities) based on tourist’ perceptions using Importance Performance Analysis (IPA) and formulated the best development recommendations for improvement as the result of Quality Function Deployment (QFD). Data were collected from 100 local and international tourists through questionnaires, and analyses revealed an average performance score of 3.53, an importance score of 4.03, and an average score of 87.45%. Within such analysis, the key aspect needing improvement among the 5A aspects are the accessibility and amenities aspect, while the remaining aspects have reached the tourists’ satisfaction. By the result, development priorities were formulated include adding more trash bins (14.26%), implementing traffic redirection (13.97%), limiting vehicle entry (13.80%), increasing cleaning staff (13.12%), building a clinic (12.57%), and adding more information board (12.00%). These recommendations aim to enhance accessibility and amenities, addressing immediate challenges while providing a model for sustainable tourism development. This research highlights the importance of targeted interventions to boost tourist satisfaction and economic contributions, offering actionable insights for stakeholders and serving as a guide for improving similar destinations.